RELIGIUSITAS, KECERDASAN EMOSI DAN PERILAKU PROSOSIAL GURU - Muryadi Muryadi; Andik Matulessy (University of Merdeka Malang, 2012)
Abstract The purpose of this research is to know whether there is a relationship between religiousity, emotional intelegence and prosocial behaviour. This research is conducted to 80 Islamic teachers of State Junior High School all around District Semen. The data is obtained by using the scala measurement of religiousity, emotional intelegence and prosocial behaviour. The result of regresi analysis shows that : (1) there is a relationship between religiousity, emotional intelegence and prosocial behaviour (F = 36,349) and p = 0,000) partially (2) there is a relationship between religiousity and prosocial behaviour (t = 2,789 dan p = 0,007) and (3) there is a relationship between emotional intelegence and prosocial behaviour (t = 5,631 pada p = 0,000). The two predictors influence 48,6% to the prosocial behaviour. Key word : religiousity, emotional intelegence and teachers prosocial behaviour